P082 Gender moderates the effects of total sleep deprivation and sleep restriction on risk preference. (7th October 2021) - Lim, J; Boardman, J; Drummond, S; Dickinson, D
Abstract: Introduction: Total sleep deprivation (TSD) affects risk preference in decision-making. However, little work has examined the effects of sleep restriction (SR), or the potentially moderating role of gender, on risk preference. Here, we investigate the effects of TSD, SR, and gender on risky decision-making. Methods: 47 healthy adults (age=24.57±5.26 years, 24F) were randomly assigned to either of 2 counterbalanced protocols: 1) well-rested (WR: 9-hours time-in-bed for 6 nights) and 30hours TSD; or 2) WR and SR (4-hours time-in-bed for 4 nights). Participants performed the Lottery Choice Task (LCT) on the last day of each week. LCT requires a series of choices between two risky gambles with different risk levels. In one block, participants sought to maximise monetary gain (GAINS), and in another block, they sought to minimise losses (LOSSES). A trial-level analysis evaluated participants' likelihood of choosing the "safer" gamble under influence of each sleep condition. Results: The version*condition*gender interaction was significant. GAINS: everyone became more risk averse during TSD. Females also became more risk averse during SR, but males did not. LOSSES: everyone became more risk seeking during SR. During TSD, females became relatively more risk averse, while males became relatively more risk seeking. Conclusion: TSD and SR had similar impacts on risk preference. However, gender moderated some effects. Women generally became more risk averse during sleep loss for both GAINS and LOSSES. Men were more risk averse for GAINS and risk seeking for LOSSES. This has implications for real-world situations where individuals are required to make risky decisions.